2022
DOI: 10.1007/s00018-022-04246-w
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of SARS-CoV-2 spike glycoprotein maturation and fusion activity by nitazoxanide: an effect independent of spike variants emergence

Abstract: SARS-CoV-2, the causative agent of COVID-19, has caused an unprecedented global health crisis. The SARS-CoV-2 spike, a surface-anchored trimeric class-I fusion glycoprotein essential for viral entry, represents a key target for developing vaccines and therapeutics capable of blocking virus invasion. The emergence of SARS-CoV-2 spike variants that facilitate virus spread and may affect vaccine efficacy highlights the need to identify novel antiviral strategies for COVID-19 therapy. Here, we demonstrate that nit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 89 publications
4
28
0
Order By: Relevance
“…Another intriguing hypothesis to be considered is that, due to the high cell–cell fusion activity of its spike protein [ 102 , 103 ], the SARS-CoV-2 virion or some of the virus components may spread through cell–cell contact. This insidious strategy, which is adopted by other RNA viruses, including the respiratory syncytial virus, the measles virus [ 104 ] and the human immunodeficiency virus [ 105 ], allows the pathogen to spread in a particle-independent way, promoting immune evasion [ 106 ].…”
Section: Mechanisms Of Pathogenesis: Virus Persistencementioning
confidence: 99%
“…Another intriguing hypothesis to be considered is that, due to the high cell–cell fusion activity of its spike protein [ 102 , 103 ], the SARS-CoV-2 virion or some of the virus components may spread through cell–cell contact. This insidious strategy, which is adopted by other RNA viruses, including the respiratory syncytial virus, the measles virus [ 104 ] and the human immunodeficiency virus [ 105 ], allows the pathogen to spread in a particle-independent way, promoting immune evasion [ 106 ].…”
Section: Mechanisms Of Pathogenesis: Virus Persistencementioning
confidence: 99%
“… 485 Riccio et al demonstrated that nitazoxanide could hamper the glycosylation of SARS-CoV-2 S protein, thus hindering infectivity of the virus. 486 This study also revealed that nitazoxanide is equally effective against different variants of SARS-CoV-2, including the Delta variant. According to a preprint provided by Miorin et al, nitazoxanide exhibited an IC 50 of 4.04 μM in Vero E6 cells against SARS-CoV-2, and a significant inhibitory effect was observed in different human cell lines including stem cell-derived human alveolar epithelial type 2 cells.…”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 65%
“…The direct anti-SARS-CoV-2 effect of NTZ was not confirmed, though a recent study revealed that NTZ may interfere with N -glycosylation of SARS-CoV-2 spike protein [ 60 ]. Likewise, Riccio et al [ 61 ] observed that NTZ blocks the maturation of SARS-CoV-2 spike protein and fusion activity with ACE2 with an effect independent of emergence spike variants (Riccio et al, 2022). Therefore, NTZ might be an effective agent used in the prophylaxis and treatment of mild to severe SARS-CoV-2 infection including the variant strains.…”
Section: Immunological Effects Of Ntz In Covid-19mentioning
confidence: 99%